Questioning Skills of Prospective Teachers in Collaborative Microteaching - Sri Rahayuningsih; Febi Dwi Widayanti; Nukhan Wicaksana Pribadi; Eko Yuniarto; Steven Christian; Yunasa Pinkan Sahara; Sikky El Walida; Retno Marsitin; Isbadar Nursit (Jurnal Pendidikan dan Pengajaran, 2026)
Prospective teachers' questioning skills tend to be dominated by low-level thinking questions. This condition indicates that the learning practices carried out have not optimally encouraged students' critical thinking skills. This study aims to analyze the questioning skills of prospective teachers through the implementation of collaborative microteaching. This study used a mixed-methods approach with a case study design involving students of the Mathematics Education Study Program participating in the Microteaching course. The research subjects were selected purposively based on their involvement in the entire microteaching cycle. Data were collected through observations of teaching practices using observation sheets based on the revised Bloom's Taxonomy with instruments in the form of a questioning skills assessment rubric and structured observation guidelines, then analyzed descriptively qualitatively and quantitatively. The main results of the study indicate that the majority of students are in the category of good and very good questioning skills (72.7%), with advantages in question clarity and appropriateness to learning objectives, but the use of higher-level questions and the utilization of feedback are still limited. The implications of this study indicate that collaborative microteaching is effective as a reflective and collaborative learning environment in improving the quality of pedagogical questions, so that its integration in teacher education contributes to strengthening pedagogical competence and the quality of learning interactions.